Human Resources Development Strategy and Educator Professionalism - Bunaya (COMPETITIVE: Journal of Education, 2024)
Educational institutions are the main capital for creating education with quality human resources. Basically, human resources are a factor that can determine the achievement of success, because in any case, educational progress is determined by the human resources that are monitored. This illustrates that the existence of technology, no matter how sophisticated and modern, will not be achieved if the human resources are not qualified in organizing and managing an activity, then human resources become an influential subject in handling and controlling educational progress, if this can be implemented, the vision, mission and goals of education can be achieved effectively and efficiently. There are several things that must be done to improve the professionalism of educators in realizing the professionalism of educators in teaching. These are pre-service education, in-service and in-service training programs. With these programs, education, so that the learning activities carried out can contain effective results to achieve the expected goals which are supported by the strategy for developing educators' professionalism through professional development efforts.